Network template-based cross-linked Poly(methyl methacrylate)/tin(IV) oxide nanocomposites for the photocatalytic degradation of MB under UV irradiation - Nazeeha S. Alkayal; Hanan Altowairki; Abeer M. Alosaimi; Mahmoud A. Hussein (Journal of Materials Research and Technology, 2022)
Novel nanocomposites, m-phenylenediamine poly (methyl methacrylate)/tin(IV) oxide(m-PDA-PMMA/SnO2), were synthesized and applied to the degradation of methylene blue (MB) dye under UV light. The nanocomposites were produced using an in situ polymerization process with PMMA and m-phenylenediamine, which was used as a cross-linker. Different ratios of SnO2 nanoparticles were loaded with 2, 5, 10, and 20 wt%. FT-IR, SEM, EDX, XRD, and TGA were used to characterize the new nanocomposites. The photocatalytic properties of methylene blue (MB) dye degradation under UV light were studied. The effects of the parameters of MB concentration, nanocomposite loading, and initial solution pH were investigated. The results clearly showed that the prepared nanocomposite containing 2% and 5% SnO2 had an excellent degradation efficiency compared to the other nanocomposites. We observed that the m-PDA-PMMA1/SnO2 and m-PDA-PMMA2/SnO2 nanocomposites, under UV light, showed 99.6% and 95.3% degradation of MB dye within 120 min, respectively. The m-PDA-PMMA1/SnO2 and m-PDA-PMMA2/SnO2 nanocomposites are therefore promising catalysts for the treatment of polluted water.